(untitled) (Global Journal of Science Frontier Research, 2021)
In this paper, a hypothesis is proposed, that something similar to what happen to the puzzle of the energy losing in decay of neutron may also occur to the puzzle of the sum losing of the z-components of spin angular momenta in the synthetic course of spin coupling in Spin Topological Space. The former puzzle is related to hidden neutrial antineutrino that carries a small amount of energy away, the latter puzzle is related to hidden "constructive" zero-spin particle playing the role of a force-mediator that carries some amount of spin angular momentum, which just offsets the same amount of angular momentum losing in the formation of spin coupling.